2019
DOI: 10.17352/2455-8400.000046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water depth on growth performance of Indian major carps at a poly culture system in Bangladesh

Abstract: The main aim of this study was to assess the effect of water depth on the growth performance (length and weight) of table size Indian major carp (Gibelion catla, Labeo rohita, and Cirrhinus mrigala) fi shes. Fishes were recorded under different depth (1.20 m, 1.80 m and 2.80 m) for about eight months from February 2016 to September 2016. Water depth was considered as treatment 1 (T 1 ) for 1.20 m, treatment 2 (T 2 ) for 1.80 m and treatment 3 (T 3 ) for 2.80 m, respectively. Randomized Complete Block Design (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…These results confirmed earlier research that tank water level significantly affects the growth rates of fish in RAS, such as pikeperch (Koz³owski et al 2009), Atlantic salmon (Einarsdóttir and Nilssen 1996), and brown trout (Salmo trutta) (Flodmark et al 2004). The effect of water depth was also noted with regard to the growth performance of three species of Indian major carp (Gibelion catla, Labeo rohita, Cirrhinus mrigala) (Hosen et al 2019) and Nile tilapia (Ali et al 2013) in ponds.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These results confirmed earlier research that tank water level significantly affects the growth rates of fish in RAS, such as pikeperch (Koz³owski et al 2009), Atlantic salmon (Einarsdóttir and Nilssen 1996), and brown trout (Salmo trutta) (Flodmark et al 2004). The effect of water depth was also noted with regard to the growth performance of three species of Indian major carp (Gibelion catla, Labeo rohita, Cirrhinus mrigala) (Hosen et al 2019) and Nile tilapia (Ali et al 2013) in ponds.…”
Section: Discussionmentioning
confidence: 96%
“…In aquaculture studies, little attention has been paid to tank water level, which is a crucial factor affecting the growth, survival, yield, and welfare of fishes. While there are several studies on the impact of water levels on the survival, growth, and behavior of different fish species in recirculating aquaculture systems (RAS) (Einarsdóttir and Nilssen 1996, Flodmark et al 2004, Koz³owski et al 2009, more attention has been focused on water depths in ponds (El Naggar et al 2006, Ali et al 2013, Hosen et al 2019, Abdel-Hay et al 2020) and the impact of water level fluctuations on the species communities in rivers, lakes, and reservoirs (Kahi et al 2008, Bucat et al 2012. In pikeperch tank water levels might affect its growth, because this species takes feed mainly from the water column (Zakêoe 2009, Koz³owski et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the summer season, the water depth in fishponds can reduce up to 100 cm and sometimes lower than that. Surprisingly, tilapia can easily survive in water depths as shallow as 50 cm, though suitable growth was recorded at around 100 cm water depth [89], whereas carp need a minimum of 180 cm water volume in the pond for their suitable growth [90]. Thus, it can be presumed that tilapia can adapt to lower water volumes than other species due to drought condition and rainfall variation.…”
Section: Drought Conditionmentioning
confidence: 99%
“…It's largely due to food supply and environmental suitability (Funk et al 2020;Hvas et al 2021;Abdul Azeez et al 2021). Hosen et al (2019) have determined the optimal depth of survival for certain fish species in the Indo-Bangladesh flood plain environment. Hosen et al (2019) found that 1 to 2 m for Tilapia fish, 1 to 3 m for Shrimp fish, more than 2.14 m for cat fish and 1.2 and 2.8 m for carp fishes (Labeo Rohita, Gibelion Catla, Cirrhinus Mrigala) are optimum depth of survival.…”
Section: Introductionmentioning
confidence: 99%
“…Hosen et al (2019) have determined the optimal depth of survival for certain fish species in the Indo-Bangladesh flood plain environment. Hosen et al (2019) found that 1 to 2 m for Tilapia fish, 1 to 3 m for Shrimp fish, more than 2.14 m for cat fish and 1.2 and 2.8 m for carp fishes (Labeo Rohita, Gibelion Catla, Cirrhinus Mrigala) are optimum depth of survival. Hydrological change is a direct cause of changing water depth and availability of water in wetlands, which is linked to fish habitat quality and storage.…”
Section: Introductionmentioning
confidence: 99%